2023
DOI: 10.3389/fonc.2023.1107384
|View full text |Cite
|
Sign up to set email alerts
|

Cancer, more than a “COVID-19 co-morbidity”

Abstract: Patients with cancer represent a particularly vulnerable population at risk of adverse outcomes related to COVID-19. Collectively, the initial studies, including patients with and without cancer, confirmed that patients with cancer had a higher risk of complications and death related to COVID-19. Subsequent studies on patients with COVID-19 and cancer investigated patient and disease-related factors associated with COVID-19 severity and morality. Multiple interconnected factors include demographics, comorbidit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 112 publications
0
3
0
Order By: Relevance
“…According to a study on the impact of solid cancer on in-hospital mortality in COVID-19 patients, the 30-day in-hospital mortality rate was found to be higher in patients with solid cancer (31.7%) compared to those without cancer (20.0%) ( 51 ). Cancer not only serves as an independent risk factor for the COVID-19 disease severity ( 51 ), but also increases the risk of mortality ( 52 ). The International Severe Acute Respiratory and Emerging Infections Consortium (ISARIC) reported a significant difference in mortality rates between cancer and non-cancer patients (40.5% vs. 28.5%, respectively) ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…According to a study on the impact of solid cancer on in-hospital mortality in COVID-19 patients, the 30-day in-hospital mortality rate was found to be higher in patients with solid cancer (31.7%) compared to those without cancer (20.0%) ( 51 ). Cancer not only serves as an independent risk factor for the COVID-19 disease severity ( 51 ), but also increases the risk of mortality ( 52 ). The International Severe Acute Respiratory and Emerging Infections Consortium (ISARIC) reported a significant difference in mortality rates between cancer and non-cancer patients (40.5% vs. 28.5%, respectively) ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…Tobacco is known to be a cancer-causing substance. Other proven causes of cancer are genetic mutations or environmental factors [ 7 ]. The American Cancer Society reported that the number of new cancer cases in the United States declined during 2019 and 2020 (by 1.5%), during the pandemic era [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other proven causes of cancer are genetic mutations or environmental factors [ 7 ]. The American Cancer Society reported that the number of new cancer cases in the United States declined during 2019 and 2020 (by 1.5%), during the pandemic era [ 7 ]. This delay could cause an upward shift in the prevalence data because incidence was not immediately treated.…”
Section: Introductionmentioning
confidence: 99%